2016
DOI: 10.1016/j.apt.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Development of an empirical wall-friction model for 2D simulations of pseudo-2D bubbling fluidized beds

Abstract: A. (2016). Development of an empirical wallfriction model for 2D simulations of pseudo-2D bubbling fluidized beds. Advanced Powder Technology, 27(2), pp. 521-530.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…• v i I is the stress tensor for phase i. To account for the effect of the front and rear walls of the pseudo−2D bed, the extra body force term f f ric is incorporated in Equation 4, as proposed by Hernández-Jiménez et al [31]. This term can be neglected for the gas phase as it is expected to have a comparatively minor effect.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…• v i I is the stress tensor for phase i. To account for the effect of the front and rear walls of the pseudo−2D bed, the extra body force term f f ric is incorporated in Equation 4, as proposed by Hernández-Jiménez et al [31]. This term can be neglected for the gas phase as it is expected to have a comparatively minor effect.…”
Section: Theorymentioning
confidence: 99%
“…The model allows for the simulations of the wall−friction effect in pseudo−2D beds using a 2D domain instead of a more computationally demanding 3D domain. The results obtained by Hernández-Jiménez et al [31] showed that the incorporation of the wall−friction model produces a clear improvement of conventional 2D simulations.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Finally, Yang et al also point to the use of simplified boundary conditions that impose a zero gradient of rotational temperature. Thisconstraint impedes the dissipation of granular energy via particle-wall friction, even though wall friction is known to be an essential influence in quasi-2D systems[75].…”
mentioning
confidence: 99%